(untitled) (JED (Jurnal Etika Demokrasi), 2017)
This research is a classroom action research that aims to improve the learning outcomes of Civics through the application of Talking Stick learning model to grade V students of SD Negeri Borongkaluku Bontomarannu District, Gowa District. The subjects of this study consisted of 20 students. This research was conducted in two cycles. Cycle I and cycle II are held three times each meeting. Data collection techniques used are the test at the end of the cycle in accordance with the material being taught. Observation at the time of learning takes place. And the data collected were analyzed by using descriptive statistical analysis. The results showed that there is an increase in learning outcomes with success indicator that is individual students reach the minimum mastery criteria of 65. The average score obtained is that in cycle I 63.25 with low categorization achievement and on the second cycle 80.25 with the achievement of categorization high. Keywords: Learning Outcomes, Learning Model, Talking Stick